FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT DALAM PEMANFAATAN HERBAL DI DESA PILOHAYANGA BARATKECAMATAN TELAGA KABUPATEN GORONTALO - Sabirin B. Syukur; Rini Asnawati (-, 2021)
The Factors that Influence the Society in Utilization of Herbal in the village of West Pilohayanga su-district of Telaga Gorontalo Regency Gorontalo Province.Herbs are natural ingredients that are useful to increase endurance and can treat various diseases. The purpose of this research to determine the factors that influence the society in using of herbal in the village of West Pilohayanga sub-district of Telaga Gorontalo Regency. Design research using descriptive survey with cross sectional approach. Sampling used random sampling technique systematic sample of 36 respondents. The society use herbal 61.1%, good knowledge society 69.4%, the society habit 58.3%, high-income society 19.4%. After statistical test showed knowledge p value = 0.043, habit p value = 0.028, and revenue p value = 0.005. Conclusion there is has the influence of knowledge, there is the influence of habit, and there is has the inluence of income on the utilization of herbals.